Improved Epitaxy of AlN Film for Deep‐Ultraviolet Light‐Emitting Diodes Enabled by Graphene. Issue 23 (16th April 2019) - Chen, Zhaolong; Liu, Zhiqiang; Wei, Tongbo; Yang, Shenyuan; Dou, Zhipeng; Wang, Yunyu; Ci, Haina; Chang, Hongliang; Qi, Yue; Yan, Jianchang; Wang, Junxi; Zhang, Yanfeng; et al.
Abstract: The growth of single‐crystal III‐nitride films with a low stress and dislocation density is crucial for the semiconductor industry. In particular, AlN‐derived deep‐ultraviolet light‐emitting diodes (DUV‐LEDs) have important applications in microelectronic technologies and environmental sciences but are still limited by large lattice and thermal mismatches between the epilayer and substrate. Here, the quasi‐van der Waals epitaxial (QvdWE) growth of high‐quality AlN films on graphene/sapphire substrates is reported and their application in high‐performance DUV‐LEDs is demonstrated. Guided by density functional theory calculations, it is found that pyrrolic nitrogen in graphene introduced by a plasma treatment greatly facilitates the AlN nucleation and enables fast growth of a mirror‐smooth single‐crystal film in a very short time of ≈0.5 h (≈50% decrease compared with the conventional process), thus leading to a largely reduced cost. Additionally, graphene effectively releases the biaxial stress (0.11 GPa) and reduces the dislocation density in the epilayer. The as‐fabricated DUV‐LED shows a low turn‐on voltage, good reliability, and high output power. This study may provide a revolutionary technology for the epitaxial growth of AlN films and provide opportunities for scalable applications of graphene films. Abstract : Guided by density functional theory (DFT) calculations, a N2 ‐plasma‐treated graphene buffer layer is developed to grow high‐quality AlN for deep‐ultraviolet light‐emitting diode (DUV‐LED) applications. The plasma treatment of graphene can facilitate AlN nucleation, thus increasing the growth rate of the AlN film and improving the film quality. The as‐fabricated LED shows a low turn‐on voltage, good reliability, and high output power.